NOVEL THERMO-PVD CONSOLIDATION TECHNIQUE FOR SOFT SOILS - C. Pothiraksanon; D. T. Bergado; H. M. Abuel-Naga; S. Hayashi; Y. J. Du (Lowland Technology International, 2007)
Previous research efforts on investigating the thermo-hydro-mechanical behaviour of fine grained soils as well as recent extensive experiments conducted on soft Bangkok clay have demonstrated that saturated fine-grained soils subjected to temperature less than boiling point of water (100OC) undergo volumetric and shear strength changes depending on the stress history. These features encouraged employing the thermal load only, up to 90OC, or in combination with mechanical loading as ground improvement technique. This paper addressed the applicability of this technique through a series of large oedometer tests conducted on soft Bangkok clay. Heating was achieved using flexible wire heater attached to the PVD point or using separate line heat source. The clay has been subjected to either thermal load or thermo-mechanical load. The test results show that a combination of the thermal and mechanical load gives promising results and is a viable technique since it accelerates the rate of consolidation and increases the amount of total settlement. This behavior can be attributed to the increase in the soil hydraulic conductivity as the soil temperature increases. Therefore, raising the soil temperature during the preloading period can enhance the performance of the PVD, particularly, by reducing the drainage retardation effects due to the smear zone around PVD.